Concentration of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) of Asian catfish oil by urea complexation: Optimization of reaction conditions - Thammapat P. (2017)
© 2016, Prince of Songkla University. All right reserved. Optimization of the concentrating conditions of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) extracted from Asian catfish oil was studied to obtain a maximum concentration. The crude fish oil was extracted from the belly flap and adipose tissue of Asian catfish, and the extracted oil was used as fresh crude oil. The EPA and DHA were concentrated by the urea complexation method. A hexagonal rotatable design was applied to examine the effects of crystallization temperature and urea-to-fatty acid ratio on the total content of EPA and DHA (Y 1 ) and the liquid recovery yield (Y 2 ). The second order polynomial regression models for Y 1 and Y 2 were employed to generate the response surfaces. Under the optimum conditions of-20 °C and a urea-to-fatty acid ratio of 4 (w/w), the total concentration of EPA and DHA could be increased by up to 88%, while a liquid recovery yield of 26% was obtained.